(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
Diabetes mellitus is a chronic endocrine disease characterized by a persistent increase in blood glucose levels due to absolute or relative insulin deficiency. The disease is widespread worldwide and is accompanied by the development of severe vascular and metabolic complications, leading to disability and a decrease in the quality of life of patients. The article examines the main forms of diabetes mellitus, causes and mechanisms of development, clinical manifestations, diagnostic methods, modern approaches to treatment and prevention of the disease.